Plasmodium falciparum Parasite Lines Expressing DC8 and Group A PfEMP1 Bind to Brain, Intestinal, and Kidney Endothelial Cells - Ortolan, Luana S.; Avril, Marion; Xue, Jun; Seydel, Karl B.; Zheng, Ying; Smith, Joseph D. (Frontiers in Cellular and Infection Microbiology, 2022)
Cytoadhesion of Plasmodium falciparum-infected red blood cells is a virulence determinant associated with microvascular obstruction and organ complications. The gastrointestinal tract is a major site of sequestration in fatal cerebral malaria cases and kidney complications are common in severe malaria, but parasite interactions with these microvascular sites are poorly characterized. To study parasite tropism for different microvascular sites, we investigated binding of parasite lines to primary human microvascular endothelial cells from intestine (HIMEC) and peritubular kidney (HKMEC) sites. Of the three major host receptors for P. falciparum, CD36 had low or negligible expression on primary microvascular endothelial cells isolated from the human brain, intestine, or peritubular kidney; endothelial protein C receptor (EPCR) had the broadest constitutive expression; and intercellular adhesion molecule 1 (ICAM-1) was weakly expressed on resting cells and was strongly upregulated by TNF-α on all three endothelial cell types. By studying parasite lines that were previously selected on an immortalized human brain endothelial cell line or isolated from a pediatric cerebral malaria patient, we provide evidence that the DC8 subset of the P. falciparum erythrocyte membrane protein 1 (PfEMP1) family encodes binding affinity for brain, intestinal, and peritubular kidney endothelial cells and that parasite adhesion was partially dependent on EPCR. Collectively, these findings raise the possibility that DC8 EPCR-binding PfEMP1 variants may contribute to multi-organ sequestration and complications in severe malaria.